1991
DOI: 10.1161/01.str.22.8.993
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy study of the incidence of lacunes in relation to age, hypertension, and arteriosclerosis.

Abstract: We investigated selected features of lacunes in 1,086 necropsy cases. Lacunes were found in brains from patients above the age of 40 years and were most common in brains from persons in their sixties but decreased in number in brains from older persons. The most common site of lacunes was the frontal lobe white matter, followed by the pntamen, pons, parietal lobe white matter, thalamus, and caudate nucleus in descending order of frequency. By dividing the 1,086 cases into three groups according to blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…15 These pathogenetic features are similar to those seen in lacunar infarction. 16 Our patients had chronic hypertension and had experienced lacunar infarction or deep basal minor hemorrhage, suggesting the presence of hypertension-related arteriosclerosis. The present study did not include either physically disabled or demented patients, two common results of major stroke or multiple lacunar infarction.…”
Section: Discussionmentioning
confidence: 72%
“…15 These pathogenetic features are similar to those seen in lacunar infarction. 16 Our patients had chronic hypertension and had experienced lacunar infarction or deep basal minor hemorrhage, suggesting the presence of hypertension-related arteriosclerosis. The present study did not include either physically disabled or demented patients, two common results of major stroke or multiple lacunar infarction.…”
Section: Discussionmentioning
confidence: 72%
“…Few studies used older animals or ones with pre-existing vascular problems, although most patients with lacunar stroke are older and have vascular risk factors. 71 Few studies used appropriate neurological/behavioral tests to assess physiological/cognitive impairments. Clinical examination for "lacunar syndromes" 38 is the first assessment of a potential patient with human lacunar stroke.…”
Section: Discussionmentioning
confidence: 99%
“…269,270 Narrowing and sclerosis of small penetrating arteries in the subcortical regions of the brain are common findings on autopsy in chronic hypertension. [271][272][273][274] These changes are believed to contribute to hypoperfusion, loss of autoregulation, compromise of the blood-brain barrier, and ultimately to subcortical white matter demyelination, microinfarction, and cognitive decline. MRI studies in persons with chronic hypertension have revealed greater numbers of subcortical white matter lesions and microinfarcts, astrogliosis, ventricular enlargement, and extracellular fluid accumulation than in agematched controls.…”
Section: Cognitive Function and Dementiamentioning
confidence: 99%